Local fractal dimension of collagen detects increased spatial complexity in fibrosis - Dylan T. Casey; Karolyn G. Lahue; Vitor Mori; Jacob Herrmann; Joseph K. Hall; Béla Suki; Yvonne M. W. Janssen-Heininger; Jason H. T. Bates (Histochemistry and Cell Biology, 2024)
Increase of collagen content and reorganization characterizes fibrosis but quantifying the latter remains challenging. Spatially complex structures are often analyzed via the fractal dimension; however, established methods for calculating this quantity either provide a single dimension for an entire object or a spatially distributed dimension that only considers binary images. These neglect valuable information related to collagen density in images of fibrotic tissue. We sought to develop a fractal analysis that can be applied to 3-dimensional (3D) images of fibrotic tissue. A fractal dimension map for each image was calculated by determining a single fractal dimension for a small area surrounding each image pixel, using fiber thickness as the third dimension. We found that this local fractal dimension increased with age and with progression of fibrosis regardless of collagen content. Our new method of distributed 3D fractal analysis can thus distinguish between changes in collagen content and organization induced by fibrosis.

An estate at Zincirli? Land use and resource exploitation at the Middle Bronze Age monumental building Complex DD in Zincirli, Gaziantep Province of Turkey - Katleen Deckers; Doga Karakaya; Laurel Poolman; Birgül Öğüt; Jason Herrmann; Kathryn R. Morgan; Virginia Herrmann (Archaeological and Anthropological Sciences, 2023)
Near Eastern monumental buildings once hosted institutions with a variety of economic and environmental footprints. In this article examining a Middle Bronze Age II (seventeenth century BC) building complex at Zincirli, Turkey, we integrate bioarchaeological remains with ceramic and artifactual evidence to evaluate whether this building was a specialized node in a broader network and centralized economy. Combining seed/fruit/chaff analysis with charcoal, phytolith, diatom, and spherulite investigations and zooarchaeology allows for a more holistic identification of the building’s environmental and economic catchments. The pronounced presence of conifer, probably related to the building’s architecture, suggests an elite function of the complex. A broad range of activities took place within the complex, such as the preparation, storage, and consumption of different food and drink products, alongside craft activities. There is evidence for centralized storage of diverse crops and production of wine and textiles. The building seems to have functioned as a kind of estate, possessing access to large areas of land. The bioarchaeological remains evidence the exploitation of the varied environments surrounding the site, where economically valuable resources were locally available and exploited, such as cedar, pine, grapes, and large hunting game. Complex DD provides evidence of wetland exploitation, agropastoral production, wood procurement, and hunting in the semi-steppe batha environments of the Islahiye plain and the woodland forests of the Amanus.